Efforts To Improve The Recognition Of Hijaiyah Letters Through The Tilawati Method In Group A Children At Aba 55 Kindergarten In Semarang - Oktavia, Rina (Sekolah Tinggi Agama Islam Muhammamdiyah Blora, 2025)
This study aims to improve the ability to recognize hijaiyah letters in Group A children at ABA 55 Semarang Kindergarten through the application of the Tilawati method. The background of this research is the low ability of children to recognize and pronounce hijaiyah letters, which is caused by learning methods that are less interesting and not in accordance with the characteristics of early childhood development. Learning that is monotonous and less varied causes children to get bored easily and not focus on recognizing hijaiyah letters. Therefore, a more interactive, fun, and appropriate approach is needed for the child's developmental stages. This study uses the Kemmis and McTaggart model Class Action Research (PTK) approach, which is carried out in two cycles. Each cycle consists of four stages, namely planning, implementation of actions, observation, and reflection. The subjects in this study were 7 children aged 4–5 years who were members of Group A. Data collection techniques included observation, documentation, and performance assessment. The results of the study showed a significant increase in children's ability to recognize hijaiyah letters. In the initial condition (pre-action), only 28.57% of children were in the Developing According to Expectations (BSH) category. This percentage increased to 71.43% in cycle I, and reached 85.7% in cycle II. These findings prove that the Tilawati method is effectively used in improving the recognition of hijaiyah letters in early childhood, especially in the context of Islamic religious learning in kindergarten.